Development of Automatic Storage Retrieval System for Variable Loads - Afzeri Tamsir (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Automated Storage and Retrieval Systems (ASRS) have been widely used in warehousing systems to speed up load movements and save storage space. ASRS is an integrated system that is equipped with a controller and arm for the collection and storage of goods. This paper discusses the results of developing a system for taking and storing goods for various loads. The prototype element consists of a mechanism for retrieving, placing and application for data collection into the database. In this research, the design and development of ASRS was carried out to be applied in the storage of products of various sizes which is suitable for small size industries. The development process includes investigating features that have been developed in the ASRS, operating procedures, hardware selection and software development in accordance with the mechanism designed. Numerical control which moves the carrier element with high resolution is applied to be able to place the load in a changing position. Development and testing is carried out to ensure the performance of the tool runs well and the data storage that includes the identification and size of the load can be recorded properly.